Importance of neoadjuvant treatment in management of locally advanced rectal cancer - Ljiljana Vasić (Биомедицинска истраживања, 2018)
Neoadjuvant approach or preoperative use of radiotherapy and chemotherapy in the treatment of locally advanced rectal cancer has led to a significant improvement in local control of the disease by reducing the percentage of local recidives. Furthermore, it has improved the quality of life since the number of sphincter sparing resections has been increased, while it has not affected the overall survival of patients. In the treatment of locally advanced rectal cancer, recommendations for selecting appropriate patients for this kind of treatment are based on independent prognostic factors: the stage of disease (tumor size, lymph nodes, infiltration of the mesorectal fasciae) and localization of the tumor in relation to anal verge. These prognostic factors indicate the risk of local recidive the likelihood of which is reduced by neoadjuvant treatment with sfincter sparing resection with the aim of improving the quality of life. The success of neoadjuvant treatment depends on: modality and radiotherapy treatment technique, the time at which primary tumor resection occurs, as well as tumor biology. The findings of colorectal carcinogenesis mechanisms have raised hope that molecular therapy together with new radiation techniques will provide a better response to preoperative treatment, thereby determining the choice of adjuvant therapy in order to achieve better overall survival of patients. The ongoing clinical studies will provide answers to these questions.
Keywords: rectal cancer; locally advanced stage; preoperative treatment; local recidive; overall survival